Physical phenomena and processes in freezing, frozen and thawing soils - Tsytovich, N. A.; National Research Council of Canada. Division of Building Research (National Research Council of Canada, 1964)
This translation is the eighth arranged by the Permafrost Subcommittee of the Associate Committee on Soil and Snow Mechanics of the National Research Council of Canada, of the Russian permafrost publication, "Principles of Geocryology". This translation of Chapter V by N.A. Tsytovich and several of his colleagues deals with physical phenomena and processes in freezing, frozen and thawing soils. It includes discussion of the principle components of frozen soils, the classification of moisture in frozen soils, ice content and liquid phase, equilibrium of water and ice, thermal and physical chemical characteristics, mechanical processes, and the alteration of frozen soils during freezing and thawing. Ce document est la huitième traduction consacrée à l'ouvrage russe intitulé Principes de géocryologie, qui est demandée par le Sous-comité du pergélisol du Comité associé de la mé canique des sols et de la neige du Conseil national de recherches du Canada. Cette traduction du chapitre V, écrit par N.A. Tsytovich et plusieurs de ses collègues, traite des phénomènes physiques et des processus observés dans la congé lation des sols, ainsi que dans les sols gelés et en voie de dégel. Le document contient une discussion sur les principales caractéristiques des sols gelés, et présente des tableaux indiquant les quantités d'eau dans les sols gelés, la quantité d'eau en fonction du volume de glace, les rapports d'équilibre entre l'eau et la glace, les caracté ristiques thermiques et physico-chimiques, les procédés mé caniques, et les changements subis par les sols gelés au cours du gel et du dégel. Peer reviewed: No NRC publication: Yes